A Trust Election based Mechanism for finding selfish node and preventing them from Attack - Mishra, Priya; Singh, Ompal; Bhatt, Abhishek (International Journal of Computer Sciences and Engineering, 2019)
Wireless sensor network is an important communication resource in wireless area. It enable to recognize many resources and file data such as temperature, humidity and many other dynamic functional data which needed observation. In many remote areas where the different terminology adaption is difficult while dealing with opposite situations wireless sensor network help in establish a proper communication between them. A proper network and communication also get disadvantage of intruder and anomaly within the network. WSN deals with attack resistance and finding such node which participate in such activity. Many algorithm used for finding such selfish attack nodes and preventing data from them. In this paper the proposed algorithm shown is proposed for the selfish node detection and prevention. The approach is performed using NS-2 simulation tool with dynamic node number selection model. The observe outcome while running the script observe high performance over existing scenario.